Pengaruh Strategi Pembelajaran REACT (Relate, Experiencing, Applying, Cooperating, dan Transfering) terhadap Prestasi Belajar Pendidikan Agama Islam di Madrasah - Zuliana, Zuliana; Niswa, Khairun; Rahman, Abd (Yayasan Rahmat Islamiyah, 2023)
The REACT learning strategy was introduced by the Center of Occupational Research and Development (CORD) in the United States, and it has garnered the attention of many researchers who generally study this learning strategy in the field of science subjects. Therefore, this learning strategy was designed to stimulate and attract the enthusiasm of the students in Islamic religious education, in order to facilitate their understanding and consequently improve their academic performance. This research was conducted to investigate the effect of the REACT learning strategy on students' academic achievement in Islamic religious studies at the Madrasah Aliyah. The method used was a classroom action research,